The moderating role of posttraumatic growth in secondary traumatic stress–burnout relationship: a sample of child psychiatrists from Turkey - Berhan Akdağ; Seda Bozduman Çelebi; Funda İpekten; Feyruz Usluoğlu; Serhat Nasıroğlu (Middle East Current Psychiatry, 2023)
Abstract Background Secondary traumatization is a common occupational hazard for professionals working with distressed and traumatized people, especially children. If not properly managed, secondary traumatization can lead to symptoms similar to posttraumatic stress disorder. This condition is known as secondary traumatic stress (STS) and is linked to adverse mental health outcomes, such as burnout. Nevertheless, exposure to a traumatic event or its disturbing details can contribute to personal transformation, allowing an individual to move beyond pre-traumatic functioning and awareness. This process is called posttraumatic growth and is associated with positive mental health outcomes. The current study examined the relationship between STS and burnout and whether posttraumatic growth moderates this relationship in a sample of child psychiatrists. Methods An online questionnaire was designed and distributed to participants. A total of 59 child psychiatrists working in Turkey completed measures including the Copenhagen Burnout Inventory-work burnout subscale, the Posttraumatic Growth Inventory, and the Secondary Traumatic Stress Scale. Results While STS was positively related to burnout (r = 0.661, p < .001), posttraumatic growth moderated this relationship. In other words, the relationship between STS and burnout was weaker for child psychiatrists with higher posttraumatic growth. Conclusions Promoting posttraumatic growth may be a good way to reduce burnout among child psychiatrists. Individual or group supervision can promote posttraumatic growth by providing a supportive environment for child psychiatrists. Balancing workloads and creating time for self-care can also contribute to their growth.